2020
DOI: 10.1007/s00894-020-04552-9
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and magnetic properties of naphthalene- and stilbene-diimide-bridged diuranium(V) complexes: a theoretical study

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The DFT geometry optimizations of the High Spin (HS) states, which have been carried out using the BP86 functional of Becke and Perdew, , employed triple-ζ-plus polarization (TZP) all-electron Slater-type orbitals (STO) basis sets. Our previous recent works, ,,, and several other theoretical studies , have shown that such a ZORA/BP86/TZP procedure reproduces the experimental geometries of f-element compounds with a satisfying accuracy. As recommended, , the computation of the J exchange coupling constant has been done using the standard B3LYP hybrid functional. , The B3LYP HS energies were obtained performing a single point calculation using the BP86 optimized geometries.…”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…The DFT geometry optimizations of the High Spin (HS) states, which have been carried out using the BP86 functional of Becke and Perdew, , employed triple-ζ-plus polarization (TZP) all-electron Slater-type orbitals (STO) basis sets. Our previous recent works, ,,, and several other theoretical studies , have shown that such a ZORA/BP86/TZP procedure reproduces the experimental geometries of f-element compounds with a satisfying accuracy. As recommended, , the computation of the J exchange coupling constant has been done using the standard B3LYP hybrid functional. , The B3LYP HS energies were obtained performing a single point calculation using the BP86 optimized geometries.…”
Section: Methodsmentioning
confidence: 69%
“…The DFT/BS approach based on the hybrid functional B3LYP turns out to be reliable for a satisfying estimation of the coupling constants, not only for binuclear transition metal complexes, but also for actinide-containing molecules, ,,, ,,, even though the use of the DFT single-determinant approach is a subject of debate. , Note that alternatively, the PBE0 functional has also been used to compute the coupling between an actinide (Pu VI ) and a radical (it is known that hybrid functionals usually lead to better values of coupling constants).…”
Section: Methodsmentioning
confidence: 99%
“…The DFT geometry optimizations of the High Spin (HS) states, which have been carried out using the BP86 functional of Becke and Perdew, [45,46] employed triple-ζ-plus polarization (TZP) all-electron Slater type orbitals (STO) basis sets. Such a ZORA/BP86/TZP procedure, which has been successfully used in our previous related works, [17,[25][26][27] and in several other theoretical studies, [47,48] has shown to reproduce the experimental geometries of f-element compounds with a satisfying accuracy. Moreover, the computation of the J exchange coupling constant has been done using the standard B3LYP hybrid functional [49,50] as recommended in previous studies.…”
Section: Methods a Computational Detailsmentioning
confidence: 99%
“…Therefore, efforts in this area have been devoted to synthesizing and characterizing polynuclear uranium systems, where a successful strategy for promoting electronic interactions between 5 f spin centers was to use covalently linked bridging ligands. [25][26][27][28][29][30] However, such mixed 3d-5f polymetallic compounds remain rare, and to date, there are only a few X-ray-determined structures for which a magnetic superexchange coupling constant has been measured, as was recently reviewed. [1,3,10] Furthermore, quantifying the coupling constant between 5 f ion pairs is still challenging at both the experimental and theoretical levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation